Bank recovery and resolution planning, liquidity management and fragility - Deidda, Luca G.; Panetti, Ettore (Journal of Financial Stability, 2025)
We study how regulation shapes the interaction between financial fragility and bank liquidity management, and propose a rationale for the complementarity between bank recovery and resolution planning. To this end, we analyze an economy in which a resolution authority arranges a bank resolution plan to suspend deposit withdrawals and create a “good bank” at a cost in the event of a depositors’ run. In such a framework, banks find it optimal to establish recovery plans in advance, specifying how to manage liquidity during runs. However, such plans are time inconsistent, and resolution authorities need powers to force their implementation at times of financial fragility .